Economic assessment of cellulase production in batch and semi-batch solid-state fermentation processes. (24th March 2023) - Taiwo, Abiola Ezekiel; Tom-James, Andykan; Musonge, Paul
Abstract: The vast range of applications for enzymes in the production of biofuels has led to a major increase in market demand in recent years. Cellulase's high cost and poor catalytic efficiency are two key barriers to the industrial usage of lignocellulosic biomass as feedstocks for fuels in biorefineries. In this study, the economic evaluation of cellulase production in solid-state fermentation was done by designing two process routes (batch and semi-batch) to optimize the process. SuperPro Designer Software has been used to create a process model that assessed the economics of fermentation operations while Monte Carlo Software was used to conduct the sensitivity analysis investigation. The impacts of cellulase yield, productivity, aeration rate and specific power input on the unit production cost (UPC) of cellulase enzyme were studied. The batch procedure requires more sterilized air for the aerobic fermentation process than the semi-batch approach, according to the results. In comparison to the batch fermentation process, the semi-batch approach had a payback period of less than 2 years, an internal rate of return of 39.14% and a net present value of 142 089 000. The semi-batch process approach has a higher economic feasibility when compared with the batch fermentation process since it is more certain to attain its base case value of UPC at the maximum. This research was key to developing a process pathway that reduces cellulase production costs in solid-state fermentation while improving market supply for its use in a biorefinery to produce sustainable fuel.